The potential impact of PM2.5 on the covid-19 crisis in the Brazilian Amazon region - Gonçalves, Karen dos Santos; Cirino, Glauber G.; Costa, Marcelo Oliveira da; Couto, Lucas de Oliveira do; Tortelote, Giovane G.; Hacon, Sandra de Souza (Revista de Saúde Pública, 2023)
OBJECTIVE: This study aims to assess covid-19 morbidity, mortality, and severity from 2020 to 2021 in five Brazilian Amazon states with the highest records of wildfires. METHODS: A distributed lag non-linear model was applied to estimate the potential exposure risk association with particulate matter smaller than 2.5-μm in diameter (PM2.5). Daily mean temperature, relative humidity, percentual of community mobility, number of hospital beds, days of the week, and holidays were considered in the final models for controlling the confounding factors. RESULTS: The states of Para, Mato Grosso, and Amazonas have reported the highest values of overall cases, deaths, and severe cases of covid-19. The worrying growth in the percentual rates in 2020/2021 for the incidence, severity, and mortality were highlighted in Rondônia and Mato Grosso. The growth in 2020/2021 in the estimations of PM2.5 concentrations was higher in Mato Grosso, with an increase of 24.4%, followed by Rondônia (14.9%). CONCLUSION: This study establishes an association between wildfire-generated PM2.5 and increasing covid-19 incidence, mortality, and severity within the studied area. The findings showed that the risk of covid-19 morbidity and mortality is nearly two times higher among individuals exposed to high concentrations of PM2.5. The attributable fraction to PM2.5 in the studied area represents an important role in the risk associated with covid-19 in the Brazilian Amazon region.